The broad spectrum of cancer and immunotherapy: achievements and limitations - Aman, Arifa; Toledo, Belén; González-Titos, Aitor; Picon-Ruiz, Manuel; Hernández-Camarero, Pablo (Frontiers in Immunology, 2026)
Cancer immunotherapy has revolutionized cancer treatment over the past decades, offering renewed hope to patients with previously untreatable malignancies. This therapeutic approach could be categorized into three primary strategies: immune checkpoint blockade, adoptive cell therapy, and cancer vaccines. Immune checkpoint inhibitors have been highly successful in boosting anti-tumour immune responses by blocking the immunosuppressive signals that cancer cells exploit to evade immune surveillance, mainly that exerted by cytotoxic T lymphocytes. Adoptive cell therapy, particularly chimeric antigen receptor (CAR)-T cell therapy, involves the infusion of genetically modified cytotoxic T cells to specifically target tumour cells, showing particular efficacy in hematological malignancies. Cancer vaccines have also emerged as a promising strategy, eliciting anti-tumour responses via the patient’s own immune system. Despite these advancements, several challenges persist, particularly in the treatment of solid tumours. These include the development of tumour resistance, off-target effects that lead to adverse side effects, manufacturing complications, and variability in patient clinical outcomes. Overcoming these limitations will require further research and innovation to optimize the clinical translation of immunotherapy and broaden its application toward more personalized medicine. This review highlights the advancements and key challenges in the mentioned cancer immunotherapy strategies, with a special emphasis on the reinforcement of adaptive immune system against tumour cells. Additionally, some alternative approaches relying on the modulation of innate immune system are also summarized.